Sulfated Fucogalactan From Laminaria Japonica Ameliorates β-Cell Failure by Attenuating Mitochondrial Dysfunction via SIRT1–PGC1-α Signaling Pathway Activation - Wu, Nan; Jin, Weihua; Zhao, Yuchen; Wang, Hong; He, Sunyue; Zhang, Wenjing; Zhou, Jiaqiang (Frontiers in Endocrinology, 2022)
As mitochondrial metabolism is a major determinant of β-cell insulin secretion, mitochondrial dysfunction underlies β-cell failure and type 2 diabetes mellitus progression. An algal polysaccharide of Laminaria japonica, sulfated fucogalactan (SFG) displays various pharmacological effects in a variety of conditions, including metabolic disease. We investigated the protective effects of SFG against hydrogen peroxide (H2O2)-induced β-cell failure in MIN6 cells and islets. SFG significantly promoted the H2O2-inhibited proliferation in the cells and ameliorated their senescence, and potentiated β-cell function by regulating β-cell identity and the insulin exocytosis-related genes and proteins in H2O2-induced β-cells. SFG also attenuated mitochondrial dysfunction, including alterations in ATP content, mitochondrial respiratory chain genes and proteins expression, and reactive oxygen species and superoxide dismutase levels. Furthermore, SFG resulted in SIRT1–PGC1-α pathway activation and upregulated the downstream Nrf2 and Tfam. Taken together, the results show that SFG attenuates H2O2-induced β-cell failure by improving mitochondrial function via SIRT1–PGC1-α signaling pathway activation. Therefore, SFG is implicated as a potential agent for treating pancreatic β-cell failure.